THE PRACTICE OF REINTEGRATION OF RADICALIZED INDIVIDUALS INTO SOCIETY IN FOREIGN COUNTRIES: A SOCIO-PHILOSOPHICAL ANALYSIS - Akhmedova, Iroda Shokhitbekovna (Oriental Journal of History, Politics and Law, 2026)
This article analyses the socio-philosophical meaning of the reintegration of radicalised individuals into society. Reintegration is not merely a security measure or a process of providing employment to a former prisoner. It entails restoring an individual’s place in society, social relationships, legal status, and confidence in the future. The article argues that effective reintegration should combine an individualised approach, engagement with the family, education and employment support, psychological assistance, religious counselling, local community participation, and long-term follow-up. Viewing an individual solely as a source of risk may lead to their further alienation from society. Therefore, reintegration should be based on a balance between security, human dignity, social justice, and civic responsibility.